E.E.C. Thuraisingham: A Malaysian Patriot by Joseph M. Fernando, Zulkanain Abdul Rahman and Abdullah Zakaria Ghazali. Kuala Lumpur: University of Malaya Press, 2013, 90 pp. - Viswanathan Selvaratnam (Kajian Malaysia, 2013)
Dato' Sir Ernest Emmanuel Clough Thuraisingham (1898?1979), in spite of coming from a minority Jaffna Tamil Ceylonese community of obscure origins, rose from nobody to somebody in the colonial and post-colonial Malaya/Malaysia milieu. He is reputed to have been a multi facet individual: a successful legal practitioner, rubber estate owner, devoted family man, social activist, community leader, able public speaker and debater, the founder President of the Ceylonese Federation of Malaya, race-horse enthusiast, philanthropist, a prominent political figure by virtue of his nominations to several key positions in the post-Second World War colonial administration of Malaya. His initial nomination was as member of the short-lived Malayan Union's Selangor State Council, then to the Federal Legislative Council and later as Member for Education in the Executive Council of the Federal Legislative Council, a key ministerial position in the colonial administration. He was a Senator in Independent Malaya/Malaysia. He was also appointed to serve as Chairman of the critically important Communities Liaison Committee (CLC), initially formed to alleviate the immediate causes of inter-communal friction (Means, 1970: 123). As a leading and influential national and community leader it is generally perceived that his "ideas, thoughts and actions" have had "influenced many facets" of the political and socio-economic landscape of postsecond World War colonial and early years of Independent Malaya/Malaysia (p. 73). In recognition of his services and contributions to the country during British rule he was notably rewarded with a Datukship by Sultan Ibrahim of Johore in 1950 and a Knighthood by Queen Elizabeth II of Great Britain in 1955.